2012
DOI: 10.1103/physrevb.85.064417
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial geometry dependence of the iron magnetic moment: The case of MgO/Fe/MgO

Abstract: The prediction and experimental demonstration of a very large magnetoresistance in Fe/MgO/Fe tunnel junctions have led to intense study of related systems in the last decade. In the present paper, we concentrate on the role of interface coordination, Fe thickness, and magnetization in the MgO/Fe/MgO mirror. By first-principles analysis, it is shown that the iron magnetic moment can rise up to 4 μ B , accounting for observed deviation of the Fe atoms in the vicinity of MgO interfaces. The origin is attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…First, the absence of an out-of-plane magnetization component is expected for a Fe thickness of 12 nm. 34 Second, the increase of the magnetic moment in the 2-3 ML near both MgO interfaces confirms the theoretical predictions 19,20 and is in good agreement with experimental work published for samples of only a few Fe monolayer thicknesses. 21 Indeed, theoretically, Li and Freeman demonstrated that an enhancement of 30% of the magnetic moment was expected for a 2ML Fe thick film on MgO.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…First, the absence of an out-of-plane magnetization component is expected for a Fe thickness of 12 nm. 34 Second, the increase of the magnetic moment in the 2-3 ML near both MgO interfaces confirms the theoretical predictions 19,20 and is in good agreement with experimental work published for samples of only a few Fe monolayer thicknesses. 21 Indeed, theoretically, Li and Freeman demonstrated that an enhancement of 30% of the magnetic moment was expected for a 2ML Fe thick film on MgO.…”
supporting
confidence: 88%
“…17,18 For such Fe/MgO interfaces, the hybridization between Fe and MgO has been theoretically predicted to result in a significant enhancement of the interfacial Fe magnetic moment similar to the one expected for freestanding Fe monolayers. 19,20 Experimentally these predictions have been corroborated by probing the thickness dependent total magnetic moment of 1-6 ML thick Fe films on MgO yielding indirect evidence for interfacial moment enhancement in actual device structures 16,21,22 or other substrates with similarly strong electronic hybridization. 23 There has been no experimental study probing the depth dependence of the Fe magnetic moment within a single MgO/Fe/MgO heterostructure.…”
mentioning
confidence: 80%
“…The equilibrium structures of the MgO layers on Fe(001) were optimized with an a priori assumption that the oxygen preferably adsorbs at the on-top sites. However, the calculation by Beltrán et al 35 suggested that under low MgO coverage, Fe binds to Mg rather than to O.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it focuses on spin-orbit interactions, which can be enhanced by our method, while they have been ignored in previous applications of plasmonic or photonic effects. We were motivated by the discovery of large magnetic anisotropies in ultrathin Fe/MgO films [43][44][45][46][47] . The Fe/MgO interface is used in a wide range of devices, and enhanced spin-orbit interactions are expected because of the large magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%